Sistem Monitoring IoT untuk Perawatan Preventif dan Deteksi Dini Mesin Kapal Tugboat: IoT Monitoring System for Preventive Maintenance and Early Detection of Tugboat Engines - Mangunsong, Jimmy Newtron; Ramadhan, Gilang; Hamapu, Nazarudin (PT Yupin Felicitas Utama, 2025)
This research proposes an Internet of Things (IoT)-based monitoring system to detect early damage and perform preventive maintenance on tugboat engines. Using an Arduino ATmega328 and a SIM900 GSM module, this system can combine engine temperature, lubricating oil temperature, coolant temperature, and engine vibration levels in real time. When these parameters exceed normal limits, the system will automatically alert the ship's crew to take immediate preventive action. The implementation of this system is expected to reduce the potential for engine damage and maritime accidents due to engine failure. The sensors used include K-type thermocouples, PT100/1000 RTDs, ADXL335 vibration sensors, and piezoelectric sensors. The results show that the system can provide effective warnings when temperature or vibration exceeds the specified threshold. Keywords: IoT, tugboat, Arduino, temperature sensor, vibration sensor, preventive maintenance.